Representations of girls and women in a Saudi Arabian family education curriculum: a content analysis - Aldegether, Reem A. (Frontiers in Education, 2023)
This paper reports on a content analysis of Saudi Arabian high school Family Education curriculum, examining how girls and women are represented. The textbooks were published after the launch of the Saudi Vision 2030 reform initiatives. Considering previous research on school textbooks’ contributions to youth self-image formation and confidence development, the Family Education curriculum was optimal for examining contemporary representations of Saudi girls and women. Content analysis was conducted on the Vision 2030 documents to discern specific principles of women’s empowerment. Four themes were constructed: Awareness of Women’s Rights and Responsibilities, Exclusion, Stereotypes, and Lack of Female Role Models. Together, these themes indicate inklings of positive change, as well as enduring inequality. They suggest a gap between the government’s stated drives to empower Saudi women and textbooks that effectively underrepresent women as equal partners in the country’s development. Revision of textbooks is required in light of the country’s new vision.